2017
DOI: 10.1097/md.0000000000007066
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for polycystic ovarian syndrome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Zhou et al [ 28 ] found that acupuncture improves the hot flashes in bilaterally ovariectomized women which has relationship with modulated FSH and E2 level. In addition, there are 2 metareviews showing that acupuncture is beneficial for polycystic ovarian syndrome that has association with modulated LH, LH/FSH, and testosterone [ 29 , 30 ]. Despite this, whether the acupuncture beneficial for perimenopause with depression is associated with sexual hormones remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 28 ] found that acupuncture improves the hot flashes in bilaterally ovariectomized women which has relationship with modulated FSH and E2 level. In addition, there are 2 metareviews showing that acupuncture is beneficial for polycystic ovarian syndrome that has association with modulated LH, LH/FSH, and testosterone [ 29 , 30 ]. Despite this, whether the acupuncture beneficial for perimenopause with depression is associated with sexual hormones remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review, no studies have reported the comparison of acupuncture to sham-acupuncture in terms of menstruation frequency at present. [ 35 ] In order to reduce the placebo effect of sham-acupuncture, the expectation value of the acupuncture effect will be evaluated before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have limitations, including failure to report important clinical outcomes, poor reporting of study methods, non-randomised controlled studies, small sample size and insufficient information on allocation concealment in randomised clinical trials; even the latest systematic review and meta-analysis still came to the conclusion that there is currently insufficient evidence to support the use of acupuncture for treatment of ovulation disorders in women with PCOS. 3 4 …”
Section: Contextmentioning
confidence: 99%